2021
DOI: 10.2147/jpr.s279253
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Androgens and Days per Month of Period Pain, Pelvic Pain, Headache, and TLR4 Responsiveness of Peripheral Blood Mononuclear Cells in Young Women with Dysmenorrhoea

Abstract: Purpose Women bear a disproportionate burden of persistent pain conditions when compared to men. To determine whether the hormonal environment affects the clinical experience of pain, as measured by the days per month of pelvic pain (DPelvicPM), period pain (DPeriodPM), headache (DHeadachePM) or the in vitro EC 50 for Interleukin-1β (IL-1β) release following TLR4 stimulation with Lipopolysaccharide from Peripheral Blood Mononuclear Cells (PBMCs). Findings were stratified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…It has been hypothesized that increases in SHBG result in androgen sequestration, increasing pain sensitivity, but research on the trajectory of estradiol and SHBG over time is needed to clarify whether increased SHBG is compensatory or contributes to worsening pain trajectories. 55 A handful of small studies have attempted to explore the relationship between sex steroids and pain sensitivity explicitly but have obtained different results from our study. A study of 11 healthy participants 56 reported that the only relationship between pain sensitivity and sex steroids was estradiol and thermal pain (r ¼ 0.33, p ¼ 0.06).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It has been hypothesized that increases in SHBG result in androgen sequestration, increasing pain sensitivity, but research on the trajectory of estradiol and SHBG over time is needed to clarify whether increased SHBG is compensatory or contributes to worsening pain trajectories. 55 A handful of small studies have attempted to explore the relationship between sex steroids and pain sensitivity explicitly but have obtained different results from our study. A study of 11 healthy participants 56 reported that the only relationship between pain sensitivity and sex steroids was estradiol and thermal pain (r ¼ 0.33, p ¼ 0.06).…”
Section: Discussionmentioning
confidence: 81%
“…By definition, 31 DYSB participants reported experimental bladder pain greater than 15 on a 0-100 VAS at first urge, and they had pain levels similar to BPS participants (Table 2). Participants with DYSB reported nearly as much pain at first urge (32 [24,48]) as BPS participants (43 [34,55]; p ¼ 0.091), but had significantly more bladder capacity (256 [1,94,345] vs. 192 [89,235]; p ¼ 0.018). Notably, both DYSB and BPS participants had significantly more pain at first urge than control participants (Table 2).…”
Section: Participants' Demographic Menstrual Psychological and Sensor...mentioning
confidence: 99%
“…In a group of healthy women, Bartley and Fillingim (1) found higher testosterone levels to be anti-nociceptive, and higher estrogen levels to be mildly nociceptive. To our knowledge, our research is the first to document an inverse correlation between levels of testosterone and the experience of pain in young women (5). This article outlines our recent research findings and how androgens can influence pain at different stages of life and when different pathologies are present.…”
Section: Introductionmentioning
confidence: 84%
“…Our work, as published in the Journal of Pain Medicine ( 5 ), investigated the relationship between serum levels of 10 steroid hormones and the subjective experience of dysmenorrhea-related pelvic pain symptoms ( 5 ). We used high sensitivity liquid chromatography mass spectrometry (LC-MS) assays to measure serum levels at 2 stages of a single menstrual cycle, Day 1–2 (when estrogen is baseline) and Day 7–10 (when estrogen peaks).…”
Section: Research Findingsmentioning
confidence: 99%
See 1 more Smart Citation